Selection and In-Vitro Potentials of Amylolytic Yeast from Several Ragi Tapai in West Sumatra Province - Inelvi Yulia; Adewirli Putra; Wiya Elsa Fitri; Gusliani Eka Putri (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Ragi Tapai is a starter used for the fermentation of cassava and glutinous rice to produce conventional fermented products, such as Tapai in Indonesia. Ragi Tapai contains several enzymes and microbes that help the Tapai fermentation process. The purpose of this study was to identify the most potential amylolytic yeast and in-vitro potential (amylolytic, cellulolytic, and fermentative). GPA, YEA, APB, CMCA, and  GPACaCO3 were used as a medium for selection and characterization. The result showed that in the seven samples of Ragi Tapai West Sumatra (Padang, Padang Pariaman, Batusangkar, Padang Panjang, Payakumbuh, Solok, dan Pesisir Selatan), there was three amylolytic yeast including  genera Schizosaccharomyces (1 dan 2) and 1 genus Trichosporon. In-vitro potential, showed the genera Schizosaccharomyces and Trichosporon have amylolytic, cellulolytic, and fermentative potential. Genera Schizosaccharomyces 1 has greater amylolytic potential than genera Schizosaccharomyces 2 and Trichosporon.